Transport Bias by Ocean Currents in Sedimentary Microplankton Assemblages: Implications for Paleoceanographic Reconstructions. Issue 7 (25th July 2019) - Nooteboom, Peter D.; Bijl, Peter K.; van Sebille, Erik; von der Heydt, Anna S.; Dijkstra, Henk A.
Abstract: Microfossils from plankton are used for paleoceanographic reconstructions. An often‐made assumption in quantitative microplankton‐based paleoceanographic reconstructions is that sedimentary assemblages represent conditions of the directly overlying surface water. However, any immobile particle sinking down the water column is subjected to transport by three‐dimensional currents, which results in a lateral relocation along transport. We model dinoflagellate cyst (dinocyst) transport in a high‐resolution (0.1° horizontally) global model of the present‐day ocean and compare ocean conditions in the simulated origin of sedimentary particles to that in the directly overlying water. We find that the assumption that sedimentary particles represent the overlying surface waters is in most regions not valid. The bias induced by dinocyst transport depends on ocean current strength and direction, aggregation of particles which could increase the sinking speed, and the sediment sample depth. By using realistic sinking speeds of dinocysts and aggregates, extreme biases up to approximately ±16 °C warmer or ±4 PSU saltier are found, while other regions show lower bias from particle transport. Our model results provide a way to mechanistically and statistically explain the unexpected occurrences of some dinocyst species outside of their "normal" occurrence region, such as the northerly occurrence of the allegedly sea‐ice‐affiliated dinocyst Selenopemphix antarctica . Exclusion of such outlier occurrences will yield better constrained ecological affinites for dinocyst species, which has implications for microfossil‐based quantitative and qualitative proxies for paleoceanographic conditions. We recommend paleoceanographers to a priori evaluate the (paleo)water depth, oceanographic setting, current strength, and particle aggregation probability for their sedimentary microplankton assemblages. Key Points: We simulate the lateral transport of sinking dinoflagellate cysts in the modern ocean The transport from encystment to deposition influences the oceanographic signals preserved in sedimentary dinoflagellate cyst assemblages Accounting for systematic cyst transport could improve paleoceanographic inferrences from sedimentary microplankton distributions